The Role Of Administrative Intelligence In The Promotion Of The Dimensions Of The Quality Of Health Service - Sha’ban, Farsat A.; Saleem, Vaheen I. (Humanities Journal of University of Zakho, 2014)
The research aims to define the role of intelligence in the promotion of administrative dimensions of quality of health service in government hospitals in the province of Dohuk, based on the hypothetical scheme takes into account the relationship between two variables, the two main two assumptions were built to test the relationship and effect link between the variables of the search.It was written theoretical side to search by taking advantage of the literature of the subject, was selected hospitals (Azadi, Hefei, Emergency, Eyes, Diabetes, Dental) to make the field, sample research (45) of the personnel which focus on (managers, their assistants and managers sections and units), was prepared questionnaire to collect data side of the field, and through some of the methods of statistical data were analyzed research hypotheses were tested, was the most important conclusions, the emergence of attention and care by hospital departments surveyed concept of administrative intelligence. The research found a set of the most important recommendations try to take advantage of the strengths possessed by hospitals regarding administrative intelligence that the results showed a clear impact on the service provided, especially the mental dimension of intelligence variables. Keyword: administrative Intelligence, IQ, mental, emotional intelligence, health service quality dimensions.